Burnout syndrome and fear of Covid 19 infection in workers of the Municipality of Moyobamba - García Flores, Delicia Esther (2023)
Objective: to determine the significant relationship between burnout syndrome and fear of COVID-19 infection in workers of the Moyobamba municipality. Methodology: non-experimental design, cross- sectional and correlational type, the participants were made up of 300 workers of both sexes from 18 to 55 years old, likewise the instruments that were used were the Maslach Burnout Syndrome Questionnaire and the Scale of concern for the contagion of COVID -19. Result: there is no significant correlation between burnout syndrome and fear of COVID-19 infection (Rho=0.104; p > 0.05), as well as for the dimensions of burnout syndrome: Emotional exhaustion (Rho=0.70; p > 0,05) Depersonalization (Rho=0.092; p > 0.05), Personal fulfillment (Rho=0.044; p > 0.05). Conclusion: there is no significant relationship between burnout syndrome and fear of COVID 19 infection in workers of the Municipality of Moyobamba.